2021
DOI: 10.1111/ddi.13304
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic patterns of a mangrove‐associated frog reveal its colonization history and habitat connectivity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Indeed, genetic differentiation between populations in treefrogs was likely to result from geographic barriers, demographic processes, and selective processes affecting genetic diversity distribution over the landscape. However, the genetic exchange between the closed populations within each group was likely to occur in treefrogs; the reduction in genetic exchange is consistent with the findings that a lack of gene flow barriers between the closed populations is reported in species of frogs (Guo et al 2016;Zheng et al 2021;Jin et al 2022). Indeed, we found that there is no genetic differentiation between populations within the same geographic region.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, genetic differentiation between populations in treefrogs was likely to result from geographic barriers, demographic processes, and selective processes affecting genetic diversity distribution over the landscape. However, the genetic exchange between the closed populations within each group was likely to occur in treefrogs; the reduction in genetic exchange is consistent with the findings that a lack of gene flow barriers between the closed populations is reported in species of frogs (Guo et al 2016;Zheng et al 2021;Jin et al 2022). Indeed, we found that there is no genetic differentiation between populations within the same geographic region.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, small effective population sizes ( N e ) can lead to loss of diversity and inbreeding, which can also decrease the populations' adaptive potential. Levels of genetic diversity and patterns of population differentiation in many amphibians have now been successfully assessed using genetic markers, typically microsatellites (Andersen et al., 2004; Beebee, 2005; Burns et al., 2004; Jehle et al., 2005; Nair et al., 2012; Nair et al., 2012; Yang et al., 2016; Zheng et al., 2021). As such, these studies have typically been limited to a few genetic loci, although studies based on a larger number of markers have started to emerge (e.g., Funk et al., 2018; Guo, Lu, et al., 2016; Hardy et al., 2021; Thörn et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pleistocene sea level fluctuations are one of the prevailing paradigms of diversification of land vertebrates—via sea level vicariance—in Southeast Asia 113 , 114 . Phylogeographic patterns that temporally coincide with sea-level minima and maxima have been observed in spiders 115 , freshwater fish 116 , 117 , birds 118 , frogs 119 , 120 , gekkonid lizards 121 , and shrews 122 . However, inland geological influences are a more likely explanation for some taxa.…”
Section: Discussionmentioning
confidence: 93%